2019
DOI: 10.1088/1755-1315/337/1/012039
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the fatty acid composition of naked oats of Russian selection

Abstract: The fatty acid composition of acyl lipids of 7 naked oat cultivars was studied. Lipids are source of energy and plastic material; promote metabolic processes in the body. In the grain of studied lines the content of raw lipids varied from 5.91 to 7.87 %. The main fatty acids of the investigated lines of naked oats are linoleic (36.2-38.7 %), oleic (33.5-36.7 %), palmitic (15.3-17.8 %). According to the content of oleic and linoleic fatty acids and their ratio (1: 1), lipids of naked oats belong to the oleic-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The latter has the highest percentage of MUFA since it contains 50% oats and the studies done by Batalova et al . (2019) and Culetu et al . (2021) found that MUFA is the highest category in oats sample.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The latter has the highest percentage of MUFA since it contains 50% oats and the studies done by Batalova et al . (2019) and Culetu et al . (2021) found that MUFA is the highest category in oats sample.…”
Section: Resultsmentioning
confidence: 95%
“…Control sample which contained 100% corn had the highest percentage of SFA while the lowest was for run #2. The latter has the highest percentage of MUFA since it contains 50% oats and the studies done by Batalova et al (2019) and Culetu et al (2021) found that MUFA is the highest category in oats sample. Regarding PUFA, it was the highest in control sample which is in agreement with the study of Siano & Vasca (2020) and the lowest in run #5.…”
Section: Fatty Acid Profile By Gcmentioning
confidence: 94%
“…Among all tested cereals, oat with the highest lipid percentage, as shown by Cozzolino et al [13], was unique because of their high oil content. Studies [9,16,17] showed also in different oat cultivars that the lipid content ranged from 5 to 8%; it makes the oat a potentially oilseed crop.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of oat oil includes essential fatty acids (FAs) indispensable for humans: unsaturated ones, such as linoleic (C18: 2, ω-3) and linolenic (C18:3, ω-3), as well as arachidonic acid (C20:4, ω-6), together composing the so-called vitamin F [ 29 ]. An important indicator of the nutritional value of oat oil is the content of α-linolenic acid (C18:3), a polyunsaturated omega-3 FA, which plays an important role in the prevention of atherosclerosis [ 30 , 31 ]. A study of the naked oat lines developed in the Volga-Vyatka region showed that the lipid content in their grain varied from 5.91 to 7.87%, averaging 6.9 ± 0.98%.…”
Section: Bioactive Components In Oat and Barley Grain Used In Functional Nutritionmentioning
confidence: 99%